Design of tailored response biomaterials for controlled release of bio-reagents in diagnostic devices - Cheng, Ting (2017)
Chemical release kinetics from polymeric matrix can be modified by changing physical or chemical properties of polymers. However, it is pre-determined with the fabrication of the drug delivery system and cannot be modified further once launched. Herein polymer based release systems with tunable release kinetics adjusted via pulse width modified optical stimulation have been developed and satisfied following conditions :1) tunable release kinetics; 2) on demand release and 3) sustained controllable period. Polyesters (poly (DL-lactide-co-glycolide)/PLGA, poly lactic acid/PLA) were fabricated into thin films (<50 µm) with additives of photocatalytic nanoparticles, LiYF4 upconversion nanoparticles (UCNP), or combination thereof and irradiated with either ultraviolet (UV) light (365 nm) light emitting diodes or near infrared (NIR) light (980 nm) laser diodes at varied duty cycles. Photocatalytic nanoparticles can generate free radicals under UV light irradiation. UCNP is feasible of converting NIR radiation to UV radiation. When compared to non-irradiated polyester (PLGA) thin film without photocatalytic nanoparticles, UV (2.6±0.3 mW/cm2) irradiated polyester thin film with photocatalytic nanoparticles showed 10 times higher release kinetics and NIR (42±3 mW/cm2) irradiated polyester thin film with both photoadditives had enhanced release kinetics up to 30 times for an extended release period of 28 days. Tunable release kinetics had been achieved via adjusting duty cycle applied. UV/NIR induced photocatalysis reaction had modified release kinetics. Polyester matrix had been changed to PLA and irradiated with 110±3 mW/cm2 NIR irradiation. Polyester films displayed a 500 times increase in drug release from the NIR irradiated polyester/photoadditive film compared to non-irradiated polyester films for 17 days with photocatalysis as primary degradation mechanism. Release kinetics had reduced to 1/20 upon removal of NIR irradiation afterwards for the subsequent 14 days. On-demand release over extend period of 31 days had been achieved. In-situ UV irradiation had been adjusted by control loading of UCNPs. However, release kinetics in synergistic system with UCNP and photocatalytic nanoparticles didn’t correlate with In-situ UV generated. Transmission electron microscopy images showed coaggregation of neat photocatalytic nanoparticle and UCNP in polyester thin film. UV light were speculated to transit from UCNP to photocatalytic nanoparticle via two energy transfer mechanisms, Förster resonance energy transfer mechanism (FRET) and reabsorption, simultaneously. Colloidal photocatalytic nanoparticle was mixed with UCNP to isolate reabsorption from FRET as nanoparticles disperse homogeneously in polyester matrix. Result suggested FRET benefits photocatalysis efficiency. Meanwhile, colloidal photocatalytic nanoparticle can be used to optimize formulation.